The pharmacovigilance of psychoactive medications in Brazil - Elisaldo Luiz de Araújo Carlini; Solange Aparecida Nappo (Brazilian Journal of Psychiatry, 2003)
OBJETIVE: The present study aimed to analyze 219 notifications of suspected adverse reactions (AR) produced by psychoactive medicaments (ARPM), notified by Brazilian psychiatrists, during a 3-month period (April 1999 up to September 2001). METHOD: A notifying card for adverse reactions possibly produced by psychoactive medications was quarterly sent to all psychiatrists affiliated to the Brazilian Association of Psychiatry. Once each notification, dully filled in, was received, the possible adverse reaction was analyzed in order to verify the causality RESULTS: The psychiatrists classified as severe 50 of the ARPMs; 150 others were not considered as severe. Among the severe ones there were 3 deaths, 12 life-threatening reactions, 26 ARPMs required or prolonged hospitalization and 9 notifications described temporary disability of the patients. Among the medications, antidepressants ranked first with 122 ARPMs being notified, followed by neuroleptics (46 ARPMs) and antiepiletic medicaments (25 ARPMs). The three main organs and systems affected by the ARs were the Central Nervous System with 102 ARs, skin and mucosa with 44 and gastrointestinal with 21 ARPMs. CONCLUSION: Considering causality, i.e., the association between the medication and the described AR, 24 cases were considered as Definite (with positive dechallenge and rechallenge, i.e., withdrawal and reintroduction of the medication) and 134 other ARPMs were classified as Probable (only dechallenge positive; only with medication withdrawal; rechallenge was not performed).